HOLOGRAPHIC DYNAMICS - Bolotin, Yu. L.; Yanovsky, V. V. (Одеські астрономічні публікації, 2012)
This paper is a brief introduction to the new physical conception - holographic dynamics. Formulated in the early 90’s of the last century, the holographic principle helped to overcome some fundamental challenges facing the traditional cosmology.